Contextual Meaning Study of Translation of Childrenâ€™s Story â€œThe Lion Kingâ€ from English into Indonesian - Suprapto, Djuria (Bina Nusantara University, 2010)
Article aimed to present study on the translation of words, phrases, expressions and sentences in a children's story.The story of